Genomic Potential of Stenotrophomonas maltophilia in Bioremediation with an Assessment of Its Multifaceted Role in Our Environment - Mukherjee, Piyali; Roy, Pranab (Frontiers in Microbiology, 2016)
The gram negative bacterium Stenotrophomonas is rapidly evolving as a nosocomial pathogen in immuno-compromised patients. Treatment of S. maltophilia infections is problematic because of their increasing resistance to multiple antibiotics. This article aims to review the multi-disciplinary role of Stenotrophomonas in our environment with special focus on their metabolic and genetic potential in relation to bioremediation and phytoremediation. Current and emerging treatments and diagnosis for patients infected with S. maltophilia are discussed besides their capability of production of novel bioactive compounds. The plant growth promoting characteristics of this bacterium has been considered with special reference to secondary metabolite production. Nano-particle synthesis by Stenotrophomonas has also been reviewed in addition to their applications as effective biocontrol agents in plant and animal pathogenesis.